Non-GVHD ocular complications after hematopoietic cell transplantation: expert review from the Late Effects and Quality of Life Working Committee of the CIBMTR and Transplant Complications Working Party of the EBMT - Inamoto, Yoshihiro (Bone Marrow Transplant, 2019)
Non-graft-versus-host disease (non-GVHD) ocular complications are generally uncommon after hematopoietic cell transplantation (HCT), but can cause prolonged morbidity affecting activities of daily living and quality of life. Here we provide an expert review of non-GVHD ocular complications in a collaboration between transplant physicians and ophthalmologists through the Late Effects and Quality of Life Working Committee of the Center for International Blood and Marrow Transplant Research and the Transplant Complications Working Party of the European Society of Blood and Marrow Transplantation. Complications discussed in this review include cataracts, glaucoma, ocular infections, ocular involvement with malignancy, ischemic microvascular retinopathy, central retinal vein occlusion, retinal hemorrhage, retinal detachment and ocular toxicities associated with medications. We have summarized incidence, risk factors, screening, prevention and treatment of individual complications and generated evidence-based recommendations. Baseline ocular evaluation before HCT should be considered in all patients who undergo HCT. Follow-up evaluations should be considered according to clinical symptoms, signs and risk factors. Better preventive strategies and treatments remain to be investigated for individual ocular complications after HCT. Both transplant physicians and ophthalmologists should be knowledgeable of non-GVHD ocular complications and provide comprehensive collaborative team care.